Metoclopramide nasal spray is effective in symptoms of gastroparesis in diabetics compared to conventional oral tablet - Parkman, H. P.; Carlson, M. R.; Gonyer, D. (Neurogastroenterology and motility, 2014)
Background Delayed gastric emptying symptoms interfere with the absorption of oral medications. Intranasal metoclopramide is being developed as an alternative to oral metoclopramide for patients with diabetic gastroparesis. Methods To compare the efficacy and safety of metoclopramide nasal spray to oral tablets in diabetic patients with symptoms of gastroparesis, this randomized, open‐label, parallel design study randomized subjects to 10 or 20 mg nasal spray or 10 mg tablet four times a day for 6 weeks. Efficacy was evaluated using a total symptom score (TSS). Key Results Eighty‐nine subjects were enrolled. For the intention to treat population, both nasal dose groups (10 and 20 mg) had lower TSS with treatment compared to the oral 10 mg group. The change from baseline in TSS for nasal 20 mg was greater than the oral 10 mg at Week 6 (p = 0.026). For the per‐protocol population, there was a significant difference in the TSS between baseline and Week 6 for both the nasal 10 mg (p = 0.026) and the nasal 20 mg (p = 0.008) cohorts compared to the oral 10 mg group. Based on the definition of a responder, 88.9% of subjects who received oral 10 mg, 91.2% who received nasal 10 mg, and 97.1% who received nasal 20 metoclopramide were classified as responders. The side‐effect profile of the metoclopramide nasal spray was favorable. More side effects, especially nausea, occurred with the oral tablets. Conclusions & Inferences Metoclopramide nasal spray offers better symptom control than metoclopramide oral tablet in diabetic patients with symptoms of gastroparesis. Metoclopramide nasal spray for use in patients with symptomatic diabetic gastroparesis. Baseline and end of study total symptom scores for individual subjects in the intent‐to‐treat (ITT) population.